Low-dose Contrast-induced Encephalopathy During Diagnostic Cerebral Angiography - Kamimura, Teppei (Intern Med, 2020)
Contrast-induced encephalopathy (CIE) is a rare complication of contrast agent use. We herein report a case of acute lacunar infarction in a 70-year-old woman. During diagnostic cerebral angiography for asymptomatic common carotid stenosis, she experienced transient drowsiness. After angiography, generalized tonic-clonic seizures occurred in her left arm and leg, with eye deviation to the left. The patient was diagnosed with CIE due to the acute onset of symptoms during angiography and characteristic computed tomography findings of high-density signaling in the cortex. Our findings suggest that it is important to pay close attention to acute neurological symptoms during and immediately after examinations, even with small amounts of contrast agents.